Text and Subtext: On the Example of Two Poems by Boris Pasternak - Venclova , Tomas (Semiotika, 2015)
A close reading of two poems by Boris Pasternak (“A Storm in July” and “To the Memory of Demon”). Both poems are considered to be inverted variants (or “antitexts”) of Russian classical poems by Fiodor Tiutchev and Mikhail Lermontov (Tiutchev‘s “Spring Storm” and Lermontov‘s “Demon,” respectively). According to the author, this technique may be typical for many other poetic texts written by Pasternak.
Keywords: text; subtext; Lermontov; Tiutchev